2019
DOI: 10.3390/ma13010138
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Water Content on Mechanical Strength and Microstructure of Alkali-Activated Fly Ash/GGBFS Mortars Cured at Cold and Polar Regions

Abstract: Negative temperature curing is a very harmful factor for geopolymer mortar or concrete, which will decrease the strength and durability. The water in the geopolymer mixture may be frozen into ice, and the water content is a crucial factor. The purpose of this paper is to explore the influence of water content on the properties of alkali-activated binders mortar cured at −5 • C. Fly ash (FA) and ground granulated blast furnace slag (GGBFS) were used as binders. Three groups of experiments with different water c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 40 publications
4
13
0
Order By: Relevance
“…The compressive strength development was associated with the formation of both binding phases (C-A-S-H and N-A-S-H) in FA/GGBFS binders, as observed from the matrix microstructure through SEM/EDS and XRD analyses. The formation of such binding phases was also observed in previous research studies on FA/GGBFS-based alkali-activated mortars and composites [9,[55][56][57][58]. The binders (without fibers) incorporating reagent 2 exhibited 2% to 18% higher 28 day compressive strength (between 39 and 57 MPa) than their reagent 1 counterparts (Figure 4a,b and Table 2) due to the formation of additional C-S-H gel formation associated with high calcium content in the system.…”
Section: Compressive Strength Of Binders Without and With Fibers Having Different Reagentssupporting
confidence: 79%
See 2 more Smart Citations
“…The compressive strength development was associated with the formation of both binding phases (C-A-S-H and N-A-S-H) in FA/GGBFS binders, as observed from the matrix microstructure through SEM/EDS and XRD analyses. The formation of such binding phases was also observed in previous research studies on FA/GGBFS-based alkali-activated mortars and composites [9,[55][56][57][58]. The binders (without fibers) incorporating reagent 2 exhibited 2% to 18% higher 28 day compressive strength (between 39 and 57 MPa) than their reagent 1 counterparts (Figure 4a,b and Table 2) due to the formation of additional C-S-H gel formation associated with high calcium content in the system.…”
Section: Compressive Strength Of Binders Without and With Fibers Having Different Reagentssupporting
confidence: 79%
“…Polymerization occurs under highly alkaline conditions when reactive aluminosilicates are rapidly dissolved, and free [SiO 4 ]-and [AlO 4 ]-tetrahedral units are released in solution. The tetrahedral units are alternatively linked to polymeric precursors by sharing oxygen atoms, forming polymeric Si-O-Al-O bonds [1,9]. The development process of geopolymers uses 60% less energy and produces 80 to 90% fewer greenhouse gases than the synthesis of ordinary Portland cement (OPC)-based binders [7][8][9][10][11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the dominant geopolymer composite matrix and high water content (as compared to samples S17 and S18), cracks and corrugated wrinkles were developed during the curing and hot pressing process. The effect of water content on crack formation was proven by Wei et al [ 57 ], who concluded that the high water content in the geopolymer matrix resulted in a sudden shrinkage during the curing process, thus forming cracks. The cracks subsequently provided an opening which allowed heat to travel faster into the layers of coating and thus lower the fire retardant properties of the sample.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical and mineral composition of BBA is appropriate for reusing in the production of new, low-carbon building materials. In this way, the replacement of traditional initial material [3,4] such as fly ash or slag in alkali activated materials (AAM) by BBA leads to important environmental benefits [5][6][7]. As demand for ecological alternatives to Portland cement like alkali 2 of 13 activated materials (AAM) is growing, there is interest to utilize phosphogypsum (PG) in AAM.…”
Section: Introductionmentioning
confidence: 99%